Troxerutin, a herbal metabolite with antidiabetic and antihypercholesterolemic potential, regulates metabolic gene activity in male diabetic rats - Gul, Saira; Naseem, Mahrukh; Sheikh, Irfan Shahzad; Ali, Hafiz Muhammad; Rabbani, Imtiaz; Jamil, Tariq; Gul, Sehar; Chachar, Zaid; Ullah, Sana; Asif, Saima; Ataya, Farid Shokry; Fouad, Dalia; et al. (Frontiers in Pharmacology, 2026)
Background/ObjectiveThis study evaluated the antidiabetic and antihypercholesterolemic potential of the botanical metabolite troxerutin (TRX) and compared it with that of metformin in high-fat diet-fed streptozotocin-induced diabetic male Wistar rats.MethodsThe rats (n = 48) were divided into six groups. Diabetes was induced in the treatment groups, and different doses of troxerutin (TRX)—25 mg/kg/day (TRX25-D), 50 mg/kg/day (TRX50-D), and 75 mg/kg/day (TRX75-D)—or the standard drug (10 mg/kg/day; MET10-D) were administered for a period of 7 weeks, compared to the negative (non-diabetic control, NDC) and positive (diabetic control, DC) control groups. At the end of the trial period, serum was collected to determine the lipid profile (high-density lipoprotein, low-density lipoprotein, and very-low-density lipoprotein (VLDL)) and the concentrations of hepatic (aspartate aminotransferase and alanine aminotransferase), renal (urea and creatinine), and oxidative stress (catalase and malondialdehyde) markers. Adipose tissue, skeletal muscle, and liver tissue samples were collected to determine mRNA expression, of pro-inflammatory cytokines [tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6)] and genes involved in lipid metabolism [peroxisome proliferator-activated receptor α (PPARα), peroxisome proliferator-activated receptor γ (PPARγ), fatty acid synthase (FAS), and sterol regulatory element-binding protein-1c (SREBP-1c)].ResultsThe results showed a significant decrease (p < 0.05) in total cholesterol (TC), triglycerides (TGs), VLDL, and LDL levels, along with hepatic, renal, and stress markers, in the rats treated with a higher concentration of troxerutin (TRX75-D) compared to diabetic control rats. Moreover, troxerutin significantly (p < 0.05) upregulated the expression of PPARα and PPARγ, while the expression of FAS, SREBP-1c, TNF-α, and IL-6 genes were significantly (p < 0.05) downregulated simultaneously in the adipose tissue, skeletal muscles, and liver in a dose-dependent manner, compared to diabetic ct control rats.ConclusionTroxerutin has considerable antidiabetic and antihypercholesterolemic potential and thus could be safely used as an alternative therapeutic compound to the standard antidiabetic drug metformin.